MODEL KOMUNIKASI PEMERINTAH UNTUK KEBIJAKAN AKSELERASI PENINGKATAN STATUS PASAR TRADISIONAL - MODERN - Umi Chayatain; Saudah . (UPT Penerbitan Universitas Jember)
The article attempts to investigate a model of public communication between the government agency and social networking vendors within the traditional market in a bid to speed up the policy of altering the position of traditional market to the modern and to determine the contribution of communication traders in the market environment. Employing descriptive explanatory approach, the research whose informant are government agency official and a number of vendor tries to examine the public communication between the two parties in an effort to change the position of traditional market to the current-fashioned market. The research found that the public communication model has succeeded in tailoring a cordial partnership between themthat enables them to reach a consensus on altering the status of market. Added to that, it has brought about an effective interaction the concerned parties for accomplishing the goal. Social network traders into reinforcing the implementation of the economic activity in traditional markets. The research finding will help government agency resolve the conflict usually occur between traders and government regarding market-place status change especially when it deals with improving vendor’s social and economic empowerment.